TRANSLANGUAGING STRATEGY IN IMPROVING DESCRIPTIVE WRITING ON EFL LEARNERS’ LOW LITERACY - UMAR UMAR; ERSA ANITA AULIA; SRI ARFANI (Universitas Mahasaraswati K. Mataram, 2023)
This study focuses on the learning strategies used by lecture in teaching descriptive writing in overcoming Learning at Sumbawa Islamic High School. The purpose of this study were; 1) to find out the challenges faced by EFL learners with low literacy in improving their descriptive writing skills, and 2) the perceptions of EFL learners with low literacy regarding the use of translanguaging strategies in improving their descriptive writing skills. This research is qualitative research. Researchers used two instruments to obtain the required data, namely: observation and interviews. Based on the data obtained from the second instrument used, the following findings were obtained. First, The challenges faced by EFL learners with low literacy has five category; first, limitation of vocabulary, second complex grammar and sentence structures, third language used, fourth, learning resources, and fifth, strategy used. Language used by the teacher has the huge challenge in their learning process of descriptive writing of students of Sumbawa Islamic High School. Second, The perceptions of EFL learners with low literacy has three category; first, learning process, second, learning motivation, and third, maintaining native language. The perception of the learners regarding used translanguaging has positive contribution in teaching and learning process of descriptive writing of students of Sumbawa Islamic High School.